Double‐Sided Surface Passivation of 3D Perovskite Film for High‐Efficiency Mixed‐Dimensional Perovskite Solar Cells. (18th December 2019) - Mahmud, Md Arafat; Duong, The; Yin, Yanting; Pham, Huyen T.; Walter, Daniel; Peng, Jun; Wu, Yiliang; Li, Li; Shen, Heping; Wu, Nandi; Mozaffari, Naeimeh; Andersson, Gunther; et al.
Abstract: Defect‐mediated carrier recombination at the interfaces between perovskite and neighboring charge transport layers limits the efficiency of most state‐of‐the‐art perovskite solar cells. Passivation of interfacial defects is thus essential for attaining cell efficiencies close to the theoretical limit. In this work, a novel double‐sided passivation of 3D perovskite films is demonstrated with thin surface layers of bulky organic cation–based halide compound forming 2D layered perovskite. Highly efficient (22.77%) mixed‐dimensional perovskite devices with a remarkable open‐circuit voltage of 1.2 V are reported for a perovskite film having an optical bandgap of ≈1.6 eV. Using a combination of experimental and numerical analyses, it is shown that the double‐sided surface layers provide effective defect passivation at both the electron and hole transport layer interfaces, suppressing surface recombination on both sides of the active layer. Despite the semi‐insulating nature of the passivation layers, an increase in the fill factor of optimized cells is observed. The efficient carrier extraction is explained by incomplete surface coverage of the 2D perovskite layer, allowing charge transport through localized unpassivated regions, similar to tunnel‐oxide passivation layers used in silicon photovoltaics. Optimization of the defect passivation properties of these films has the potential to further increase cell efficiencies. Abstract : Double‐sided 2D surface passivation of 3D perovskite film contributes to a remarkable device V OC of 1.2 V, which is one of the highest open‐circuit voltages reported for perovskite cells with an optical bandgap of ≈1.6 eV. Discontinuous 2D perovskite films provide conductive pathways through these resistive layers, allowing for efficient charge transport between the 3D perovskite and charge transport layers.